The right to acquire and change Spanish nationality by foreign persons with disabilities - Moreno Sánchez-Moraleda, Ana (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Law 8/2021 of 2 June, of civil and procedural legislation reform with the intention of promoting support for persons with disabilities in the exercise of their legal capacity, has been modified the articles of the Civil Code relating to the acquisition of Spanish nationality by option, charter of nature and residence, to comply with the dictates of the 2006 New York Convention on the Rights of Persons with Disabilities. Thus, foreign persons with disabilities may declare their willingness to acquire Spanish nationality themselves with the support and procedural adjustments that may be required. We will analyze, the normative evolution and what this reform implies for foreign persons with disabilities in relation to the before Regulation.